Astute competition the economics of strategic diversity - Johnson, Peter, 1956- (Amsterdam ; Boston : Elsevier, 2007)
The first part of this book aims to provide a rigorous account of the five key strategic building blocks that underpin an analysis of heterogeneous competition. The second part deals with how these strategic concepts, embedded in various analytical techniques and tools, can illuminate strategy practice.
Cover -- Copyright page -- Contents -- Preface -- Foreword -- Abstract -- Part I: Concepts -- Chapter 1. The Economics of Strategic Diversity -- Strategy as a Solution to the Problems of Economics -- Key Elements in ESD -- The Impact of a Successful ESD on Economics -- Lasting Distinct Features of ESD -- ESD as a Fourth Leg -- Summary -- Questions -- Chapter 2. Strategic Ecology -- Strategic Ecology -- Examples of Strategic Ecology -- Other Notions of Strategic Ecology -- Ecosystem Characteristics -- Ecosystem Dynamics -- Summary -- Questions -- Chapter 3. Business Models -- How to Formalise the Intuitive Account -- Formal Interpretation of Coherence and Consistency -- An Example of the Business Model Matrices -- Application to Wireless Data Services -- Further Development of the External Attributes of the Business Model -- Internal Attributes of the Business Model -- The Application of Metrics -- Business Genomics -- Summary -- Questions -- Addendum: Strategometrics -- Chapter 4. Routes to Competitive Advantage -- Business Models -- Multiple Routes to Advantage -- Personal Career Analogy Revisited -- Modes, Themes and Contexts -- Competitive Control of Resources -- Conclusion -- Summary -- Questions -- Chapter 5. Economic Rents -- Summary -- Questions -- Chapter 6. The Return on Resources -- Traditional Measures of Performance -- Resource Margins -- Investor Requirements -- Resource Margins and Economic Value Added (EVA) -- Testing of the Value Relevance of RMs -- Link to Strategic Ecology and to Business Strategy -- Summary -- Questions -- Part II: Techniques -- Chapter 7. Business Development -- Putting Adjacency to Work -- Synergies or Strategic Revision -- Strategic Revision -- Summary -- Questions -- Chapter 8. Corporate Strategy: Purpose -- Market Failures -- The Performance Enhancement of Businesses -- Synergies -- Coordination -- Business Model Engineering -- Reinforcement -- Investment and Major Initiatives -- Corporate and Business Model IP -- Recapitulation -- Summary -- Questions -- Chapter 9. Corporate Strategy: Techniques -- Portfolio Analysis -- Scenario-Based Retrospective Valuation -- Traditional Performance Measures -- Real Options -- Infinite Projections -- Retrospective Horizons -- M & A Business Logic -- M & A Screening -- Conclusion -- Summary -- Questions -- Chapter 10. Start-up Strategy -- The Entrepreneurial Concept -- The Strategy to Build the Business -- The Strategy of the Business Once Built -- A Mnemonic: the Six T's -- Summary -- Questions -- Chapter 11. Summary, Observations and Conclusion -- Executive Summary -- Major Insights -- Constraints and Practice -- Future Research -- Conclusion -- Bibliography -- Further Reading -- Subject Index -- Last Page.
Title from PDF t.p. (viewed Jan. 2, 2010).
Includes bibliographical references and index.
Keywords: Competition; Electronic books